2017
DOI: 10.1093/annonc/mdw635
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of paclitaxel, cisplatin, and veliparib in the treatment of persistent or recurrent carcinoma of the cervix: an NRG Oncology Study (NCT#01281852)

Abstract: Background: Preclinical studies demonstrate poly(ADP-ribose) polymerase (PARP) inhibition augments apoptotic response and sensitizes cervical cancer cells to the effects of cisplatin. Given the use of cisplatin and paclitaxel as first-line treatment for persistent or recurrent cervical cancer, we aimed to estimate the maximum tolerated dose (MTD) of the PARP inhibitor veliparib when added to chemotherapy.Patients and methods: Women with persistent or recurrent cervical carcinoma not amenable to curative therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Contribution of PARP1 in regulation of metastatic events has also been thoroughly investigated in DNA repair independent manner in lung cancer via S100A4 and in melanoma via regulation of vimentin expression 19 21 . Recent phase I trial of PARP inhibitor in combination with cisplatin and paclitaxel shows well tolerance and promising results in both persistent and recurrent cervical cancer 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Contribution of PARP1 in regulation of metastatic events has also been thoroughly investigated in DNA repair independent manner in lung cancer via S100A4 and in melanoma via regulation of vimentin expression 19 21 . Recent phase I trial of PARP inhibitor in combination with cisplatin and paclitaxel shows well tolerance and promising results in both persistent and recurrent cervical cancer 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The study has accrued and results are pending. Veliparib has also been successfully incorporated into cisplatin and paclitaxel regimen in a phase I dose finding study in cervical cancer which achieved full doses of veliparib 400 mg twice daily for days 1e7 and MTD was not reached [19]. Despite the rational mechanism, success of PARP-platinum combinations are impaired by overlapping toxicities and attenuated dosing and are unlikely to be extensively developed.…”
Section: Platinumsmentioning
confidence: 99%
“…Across DLs, the objective response rate (RR) for 29 patients with measurable disease was 34%, at 400 mg DL the RR was 60%. Median progression‐free survival was 6.2 months and overall survival was 14.5 months (Thaker et al, ). A second study (NCT#737664) is an open‐label Phase I–II, single‐arm trial with a safety lead‐ in to estimate the antitumor activity of the combination of veliparib 10 mg administered orally twice a day on days 1–5 with topotecan (topotecan hydrochloride) 0.6 mg/m 2 administered IV once daily on days 1–5 of each cycle in women with pretreated persistent or recurrent cervical cancer.…”
Section: Parp Inhibitor In Cervical Cancermentioning
confidence: 99%
“…Among all the 17 members of PARP family, PARP1 is one of the most abundant proteins which is involved in regulation of transcriptional control, maintenance of genomic integrity, DNA repair, and regulation of apoptotic and survival balance in cells (Donawho et al, 2007;Javle & Curtin, 2011). PARP1 is abundantly localized in the nucleus F I G U R E 2 HPV infection and chronic inflammation caused cell's mutation, with consequent neoplastic transformation and cancer progression and 80% of its enzymatic activity includes PARylation of nuclear proteins, recruitment of DNA repair factors, and stabilization of chromatin for transcriptional regulation (Ossovskaya, Koo, Kaldjian, Alvares, & Sherman, 2010;Thaker et al, 2017). A recent Phase I trial of Veliparib in combination with cisplatin and paclitaxel showed well tolerance and promising results in both persistent and recurrent CC (Godon et al, 2008).…”
Section: Preclinical Datamentioning
confidence: 99%
See 1 more Smart Citation